Pengaruh Profitabilitas, Likuiditas, Sales Growth Dan Leverage terhadap Financial Distress pada Perusahaan Sub Sektor Kosmetik Tahun 2018-2023 yang Terdaftar di Bursa Efek Indonesia - Haniza Tarama Dhanti; Yulitiawati; Eka Meiliya Dona (Balance : Jurnal Akuntansi dan Bisnis, 2025)
This study aims to determine the effect of Profitability, Liquidity, Sales Growth and Leverage on Financial Distress in cosmetic sub-sector companies in 2018-2023 listed on the Indonesia Stock Exchange. The research sample consisted of five companies obtained through purposive sampling. Data analysis used descriptive statistics, classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination (Adjusted R Square). The results of the study showed that partially profitability and liquidity have a positive effect on financial distress, meaning they can reduce the risk of financial distress. Sales Growth and Leverage have no effect on Financial Distress. The high or low value of Sales Growth and Leverage owned by the company does not directly affect the company experiencing financial distress. Simultaneously Profitability, Liquidity, Sales Growth and Leverage have a positive effect on Financial Distress. This study adds information for companies to manage profitability and liquidity optimally and adds to the understanding of the factors causing financial distress.